Correlation Between Serum Thrombopoietin Level and Cirrhosis Clinical Stage in Liver Cirrhosis Patients in Mohammad Hoesin Palembang Hospital and Palembang BARI Hospital - Muhamad Ayus Astoni; Fuad Bakry; Irsan Saleh (The Indonesian Society for Digestive Endoscopy, 2015)
Background: Thrombopoietin (TPO) is a cytokine mainly produced in the liver that regulate humoral control mechanism of thrombopoesis. Presumably, TPO production is decrease in patients with liver cirrhosis which interfere platelet production. The aim of this study was to identify the correlation between serum TPO levels and the clinical stage of liver cirrhosis.Method: With analytical cross sectional design, this sudy analyzed the correlation between the serum TPO level and the clinical stage of liver cirrhosis according to Child-Pugh classification in 32 liver cirrhosis patients and 30 healthy subjects from March 2015 to August 2015. The serum level of TPO was examined using the Quantikine human TPO immunoassay.Results: There were 13 females and 19 males patients aged 19 to 67 years old. Serum TPO level were lower in patients with liver cirrhosis (65.65 ± 28.97 pg/mL) than in healthy subjects (98.16 ± 41.25 pg/mL, p 0.005). Serum TPO levels were negatively correlated with clinical stage of liver cirrhosis in a moderate strength of correlation (r = -0.516, p = 0.002). There were no correlation between serum TPO level and platelet count (r = 0.186; p = 0.309), but a significant negative correlation between the clinical stage of liver cirrhosis and platelet counts (r = - 0.361; p = 0.042).Conclusion: There was a significant negative correlation between serum TPO levels and the clinical stage of liver cirrhosis according to Child-Pugh classification.